Managing Cultural Heritage Sites in Southeastern Europe - Nared, Janez; Razpotnik Visković, Nika (ZRC SAZU, Založba ZRC, 2014)
The CHERPLAN project (CHERPLAN stands for "Enhancement of Cultural Heritage through Environmental Planning and Management") aims to provide a strong basis for ensuring compatibility and synergy between cultural heritage conservation and socioeconomic growth by fostering the adoption of a modern environmental planning approach throughout southeast Europe (SEE). The aim of environmental planning is to integrate traditional urban/spatial planning with the concerns of environmentalism to ensure sustainable development~when innovatively applied to cultural heritage sites, environmental planning's comprehensive perspective can be regarded as composed of three spheres: the built and historical environment, the socioeconomic and cultural environment, and the biophysical environment.